Süleymaniye kütüphanesi fatih bölümü 4078 numarada kayıtlı 16. yüzyıla ait bir şiir mecmuası (51a-100b) - Güleryüz, Özlem Seçkin (My University, 2008)
Şiir mecmuaları, Klasik Türk edebiyatında önemli bir yere sahiptir. Bu mecmualar içerisinde klasik edebiyata ait manzumeler bulunmaktadır. Bu şiirlerin bir kısmı birbirine nazire olarak yazılmış manzumelerdir. Bazı mecmualarda da edebi zevke hitap eden şiirler bir araya getirilmiştir. Süleymaniye Kütüphanesi Fatih 4078’de kayıtlı bir şiir mecmuasında 15 ve 16. yüzyıllarda yaşayan şairlerin şiirleri vardır. Tezimizde, bu mecmuanın 51a-100b varakları transkribe edilmiş, nazire ve tanzir kavramları hakkında bilgi verilmiştir. mecmuaları, mecmua geleneği, Klasik Türk Edebiyatı, nazire

The poetry collections (“macmua”s) has a crucial place in Classical Turkish Literature. There are some materials related to Classical literature in these collections. Some of these poetries are verse which have been written as “nazire”. However, poetries which are adressed to literary delight have been collected. There are some poetries which belong to poets who lived 15th-16th centuries, in the Süleymaniye Library Fatih collection 4078. Our thesis, 51a-100b papers of this collection are transcribed, “nazire” and “tanzir” concepts are explained. Key words: Poetry collections, tradition of “macmua”, Classical Turkish Literature, “nazire”
Keywords: Türk Dili; Türk Şiiri